2014
DOI: 10.1585/pfr.9.1402039
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Diagnostics with Tracer-Encapsulated Solid Pellet

Abstract: The diagnostics method of a tracer-encapsulated solid pellet (TESPEL) has been developed. TESPEL consists of polystyrene as an outer shell and of specific material as a tracer in the core. Owing to the advantages of the TESPEL, the following results have been successfully obtained: (1) distinctive different feature of impurity transport between the plateau and Pfirsch-Schlüter regimes depending on the impurity source location which is analyzed with the STRAHL code, (2) specific feature of a non-local thermal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Shigeru SUDO 1,2) , Naoki TAMURA 1) , Chihiro SUZUKI 1) , Hisamichi FUNABA 1,2) , Masaru TAKAGI 3) and Nakahiro SATOH A Tracer-encapsulated Solid Pellet (TESPEL) injection method has been shown to be useful for many fields of plasma diagnostics. In order to provide more flexibility for such plasma diagnostics, we are developing various types of TESPELs.…”
Section: Development Of Tespel Configurations For Plasma Diagnosticsmentioning
confidence: 99%
See 4 more Smart Citations
“…Shigeru SUDO 1,2) , Naoki TAMURA 1) , Chihiro SUZUKI 1) , Hisamichi FUNABA 1,2) , Masaru TAKAGI 3) and Nakahiro SATOH A Tracer-encapsulated Solid Pellet (TESPEL) injection method has been shown to be useful for many fields of plasma diagnostics. In order to provide more flexibility for such plasma diagnostics, we are developing various types of TESPELs.…”
Section: Development Of Tespel Configurations For Plasma Diagnosticsmentioning
confidence: 99%
“…Recently we reported two types of TESPEL configurations [1], namely, (i) thick-shell-type and (ii) thin-shelltype [2] for the accurate impurity transport diagnostics. In particular, it was shown that the impurity transport feature depends on the source location of the impurity and also on the collisionality (between impurities and bulk ions).…”
Section: Development Of Tespel Configurations For Plasma Diagnosticsmentioning
confidence: 99%
See 3 more Smart Citations